Alterations of DNA Repair and Immune Infiltration in Radiation-Induced Intestinal Injury - Jiale Li; Huanteng Zhang; Xiaoxiao Jia; Jiebing Guan; Xumin Zong; Shiqi Li; Xinran Lu; Ningning He; Huijuan Song; Kaihua Ji; Manman Zhang; Jianguo Li; et al. (Dose-Response)
Objectives The intestine exhibits high radiosensitivity and is susceptible to damage during radiotherapy for abdominal or pelvic tumors, especially at radiation doses exceeding 5 Gy, which can lead to severe gastrointestinal complications. This study aims to elucidate the mechanisms of DNA repair and immune responses in radiation-induced intestinal injury, with the goal of enhancing radiotherapy efficacy. Methods We employed weighted correlation network analysis (WGCNA) to analyze RNA sequencing data from intestinal tissues collected at various time points following irradiation, as well as from mice with targeted disruption of the NFE2-like bZIP transcription factor 2 (Nrf2) gene and their wild-type counterparts. Results Our analysis revealed enhanced DNA repair capacity and attenuated immune response 3.5 days after irradiation. Histone variants and ribosomal proteins were identified as potential contributors to DNA repair processes. We also constructed a competing endogenous RNAs (ceRNA) network including genes from both the DNA repair and immune modules and identified Akr1b8, Gsta3, and Nqo1 as radiation-effect genes regulated by Nrf2. Conclusions These findings provide valuable insights into the molecular mechanisms of radiation-induced intestinal injury and suggest potential targets for protecting normal intestinal tissue during radiotherapy. This knowledge may contribute to improved treatment outcomes and enhanced patient well-being.